Mengenang Djamaluddin Wak Ketok: Komandan Batalion Bazooka di PRRI Padang 1958-1961 - Regita Cahyani Nazra, Endah; Darmawan, Budi (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2023)
Djamaluddin Wak Ketok, a fighter who has been active since independence, played a verysignificant role in the PRRI upheaval in Padang City. This article aims to explain his life journeythrough a thematic biographical approach. This research approach consists of several stages:first, collecting sources through heuristic methods; then, critical processing and interpretation ofdata; and finally, biographical writing. The results of the research show that Djamaluddin WakKetok tenaciously faced the ground attack on Anduring by the central army, which ult imatelyforced the PRRI troops to retreat to the Karakate Hill hills. At a meeting in Pariaman during thePRRI upheaval, it was agreed to form five battalions under the Banteng Division. In this context,Djamaluddin Wak Ketok was chosen as commander of the Bazooka battalion responsible for thePadang City and Padang Outer City areas. His courage and steadfast attitude continued to shinethrough in battle, including the attack at Simpang Haru, which ultimately resulted in the loss ofhis life. All his sacrifices were made to protect the people who suffered from the cruel actions ofthe central army from the 442 Diponegoro battalion.